A New Allotrope of Carbon—Graphdiyne (g‐CnH2n−2) Boosting with Mn0.2Cd0.8S form S‐Scheme Heterojunction for Efficient Photocatalytic Hydrogen Evolution. Issue 15 (11th July 2021) - Jin, Zhiliang; Gong, Haiming
Abstract: As a new 2D carbon hybrid material, graphdiyne has attracted much attention due to its good conductivity, adjustable electronic structure, and special electron transfer enhancement properties. It has great potential in the field of hydrogen evolution by photocatalytic water splitting due to its special properties. In this paper, layered graphdiyne is prepared by crosscoupling method, using CuI instead of typical copper film as catalyst. Graphdiyne/CuI is used to modify Mn0.2 Cd0.8 S (MCS) solid solution for the first time, which greatly improves the optical properties and hydrogen production performance of the photocatalyst. The S‐scheme heterojunction constructed between graphdiyne and MCS greatly improves the transfer rate of photoinduced electrons. In addition, the results of fluorescence spectra and photoelectrochemical tests show that the nanocomposites have longer carrier lifetime, lower recombination rate, faster carrier migration rate, and lower hydrogen evolution overpotential. Therefore, the hydrogen evolution rate of the MnCdS/graphdiyne/CuI with the best performance can reach 9.904 mmol g −1  h −1, which is 4.02 times of that of pure MCS. This work not only proposes the possible mechanism of photocatalytic hydrogen production but also provides an important strategy for the application of graphdiyne in the field of photocatalytic hydrogen production. Abstract : The S‐scheme heterojunction between graphdiyne (GDY) and Mn0.2 Cd0.8 S (MCS) greatly improves the migration of photoinduced electrons. Therefore, the hydrogen evolution rate of the MnCdS/graphdiyne/CuI can reach 9.904 mmol g −1  h −1, which is 4.02 times of that of pure MCS. This work provides an important strategy for the application of GDY in the field of photocatalytic hydrogen production.